Studies on the trends of transfusion-transmissible infections in a district-level hospital in West Bengal, India - G Mukherjee; S Ghosh; A Mukherjee; T Mondal; S Mondal (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Therapeutic use of blood is the most sophisticated part of treatments in medical sciences. Transfusion of blood saves patients' lives as well as it has also the risk of infective disease, if it is contaminated. AIMS AND OBJECTIVES: The current study focuses on the status of TTI amongst the voluntary Blood donors over a period of time. MATERIALS AND METHODS: In this study, HIV, HCV, HBsAg and Syphilis (by RPR) screening test report for the year 2011 to 2017 of a district Hospital Blood Bank in West Bengal has been presented. Tests were done by ELISA and Syphilis by Rapid Plasma Reagin test. RESULTS: No significant changes in the incidence of above noted cases have been observed and no Malaria positive case was detected. CONCLUSION: This indicates a good awareness amongst the people regarding these diseases having immense public health importance.